The EVALUATION OF SOLID MEDICAL WASTE MANAGEMENT (PACKAGE AND STORAGE) IN HOSPITAL X KARAWANG REGENCY - Bunga, Venny Ulya (BAROMETER, 2024)
Medical waste, as one of the hazardous waste, must be managed properly to avoid significant negative effects to the environment. Medical waste management overall involves reduction, storage, transportation, processing and disposal of waste. Hospital X, as a generator of medical waste, is responsible to implement reduction and storage of medical waste. This article aims to do deep evaluate the medical waste management of Hospital X, especially in terms of packaging and waste storage where this kind of evaluation has not been implemented yet in previous reseearch. This study includes as descriptive research which conducted data collection technique through observation and interview with manager of health and safety environment and also the cleaning service of Hospital X. Primary data includes medical waste management of Hospitall X which will be evaluated descriptively its compatibility based on Law of Minister of Environmental Republik Indonesia 56/2015. The evaluation results that medical waste packaging procedures comply with requirements of Minister of Environment Regulation 56/2015. However, medical waste storage evaluation reveals two things that do not comply with the regulation: (1) location of storage area is prone to flooding and (2) storage room has insufficient lighting. Hospital X needs to do some mitigation such expand drainage for water storage, redesign storage area and add lights to the storage room. Medical waste management of Hospital X are continuously being improved. This shown from interview result with personal who handling medical waste and environmental health manager of hospital. The result indicating that training and monitoring-evaluation is held routinely in Hospital X.